Effect of misalignments and welding penetration on the fatigue strength of a common welded detail: SED method predictions and comparisons with codes. (November 2022) - Foti, Pietro; Crisafulli, Davide; Santonocito, Dario; Risitano, Giacomo; Berto, Filippo
Highlights: Fatigue assessment of welded joints has been performed by means of SED method. Free mesh approach is applied to evaluate the SED of notches in complex structures. Codes overestimate the effect of the intermediate plate on fatigue strength. Externally loaded attached plate root regions are the most critical. SED method allows a direct comparison of critical regions of the structure. Abstract: This work exploits the SED method to investigate the effects of the main geometrical parameters and geometrical imperfections - uncomplete penetration, axial and angular misalignment - on the fatigue strength of cruciform welded joints. The predictions by the SED method have been compared with those of the most known codes. The volume-free procedure for an easy application of the SED method has been used. The SED method has been proved to be consistent with the codes; however, the codes estimations result to be always more conservative than the SED method predictions. The SED method has been proved to be a valid tool to investigate different loading and boundary conditions and to provide useful information to evaluate the most critical point in the component.